National Strategic Project Policy in the Jokowi Era: Exploring Underrated and Overrated Projects in Indonesian Development - Amin Amin; Rafi Imam Mahir; Ida Hindarsah (Sean Institute, 2025)
The National Strategic Projects (PSN) policy is a key part of the infrastructure and economic development agenda under President Joko Widodo. This article aims to examine PSN projects considered underrated. and